Soundscape of the Old Tatar Settlement: Historical and Cultural Meanings - Kamilevna Khurmatullina, Rezeda (2021)
The study of soundscape as a tool to study national culture, national identity formation has a huge potential in the historical, cultural, musicological, pedagogical, and other broad aspects.  The Old Tatar settlement is one of the historic districts of Kazan; the architectural ensemble consisting of mosques which were the main location of social life of Tatars. However, the sound picture of the Old Tatar settlement's realities included acoustic images of various cultures and ethnicities, which contributed to the creation of a unique soundscape of the old Tatar settlement. We applied the methods of audio and video recordings, study of historical materials, descriptions, and recollections of old residents of this historical and cultural center of Kazan; the method of emotional immersion in the sound environment for recreation and linkages not only between objects of art and culture, but also between man and his object-cultural environment. The results showed that the history of the Tatar settlement is the history of the preservation of national identity. When Ivan the Terrible had conquered Kazan, all the Tatars were settled away from town. These people were given right to live only in the territory of the Old Tatar settlement.   The logical consequence of that was the consolidation of religious forces of the Tatar people, which became the main spiritual factor of preserving the national identity. Muslim clergy had taken the function of cultural force. The formation of specific acoustic space of the Old Tatar settlement was closely connected with the construction of Muslim mosques with minarets.  In addition to the ethno - confessional factors in the properties of cultural landscapes, we have identified several private cultural spaces, including: historical, linguistic, professional and folk art, everyday culture. We have identified the main elements of the soundscape of the Old Tatar settlement and came to the conclusion that soundscapes play a huge role in the holistic perception of objects of cultural heritage.